2022
DOI: 10.1007/s12144-022-02873-x
|View full text |Cite
|
Sign up to set email alerts
|

Telework satisfaction, wellbeing and performance in the digital era. Lessons learned during COVID-19 lockdown in Spain

Abstract: This study used a prospective design to examine the effects of telework satisfaction (time 1) on subjective wellbeing and self-reported performance (time 2) during the COVID-19 lockdown. Data were collected from 111 teleworkers through an online survey the first weeks of strict lockdown in Spain. Telework satisfaction showed positive direct effects on both subjective wellbeing and self-reported performance. Further, subjective wellbeing partially mediated the relationship between telework satisfaction and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 85 publications
1
40
0
Order By: Relevance
“…At the same time, some studies showed that when employees were satisfied with their telework conditions, they experienced higher subjective well-being and better self-reported performance [ 38 ]. Further, subjective well-being emerged also to partially mediate the relationship between telework satisfaction and self-reported performance [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, some studies showed that when employees were satisfied with their telework conditions, they experienced higher subjective well-being and better self-reported performance [ 38 ]. Further, subjective well-being emerged also to partially mediate the relationship between telework satisfaction and self-reported performance [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic, workers were forced mandatorily and full-time to telework (the so call crisis-induced telework) [32]. These two conditions of telework have had a great impact on employee wellbeing [33].…”
Section: Academic Staff Well-being During the Pandemicmentioning
confidence: 99%
“…Moreover, several studies investigated the perception of advantages and disadvantages of teleworking in the pandemic, but more rarely, the effect of teleworking satisfaction on well-being, with few exceptions that demonstrated its impact [33,46]. Two Italian studies showed that teleworkers in the field of education and research appreciate teleworking less, and have higher levels of psychological distress, than in other working fields [46,47].…”
Section: Academic Staff Well-being During the Pandemicmentioning
confidence: 99%
“…It should also be noted that work-life imbalances experienced by teleworkers cannot be predicted with negative well-being assessments. A study by Blahopoulou et al (2022) showed that even teleworkers with children at home, who were generally less satisfied with working from home, rated their well-being better when working at home than when working in an office. Thus, the effects of teleworking are not necessarily negative (Putri & Amran, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%